2019
DOI: 10.1021/acs.nanolett.9b02062
|View full text |Cite
|
Sign up to set email alerts
|

Removal of a Conserved Disulfide Bond Does Not Compromise Mechanical Stability of a VHH Antibody Complex

Abstract: Single-domain VHH antibodies are promising reagents for medical therapy. A conserved disulfide bond within the VHH framework region is known to be critical for thermal stability, however, no prior studies have investigated its influence on the stability of VHH antibody–antigen complexes under mechanical load. Here, we used single-molecule force spectroscopy to test the influence of a VHH domain’s conserved disulfide bond on the mechanical strength of the interaction with its antigen mCherry. We found that alth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

6
4

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 62 publications
1
31
0
Order By: Relevance
“…Atomic force microscopy (AFM) has allowed the imaging of biomolecules under physiological conditions [15][16][17][18][19] , which provides an alternative route to probe Ab-Ag interactions [20][21][22][23] . Previous studies have demonstrated the potential of AFM for imaging Abs with near-atomistic resolution [24][25][26] and its ability for quantitatively mapping nanomechanical forces of Ab-Ag interactions at the single-molecule level [27][28][29] . Recently, high-speed (HS) AFM offers up to video-rate temporal resolution, revealing certain types of dynamic processes of IgGs, e.g., walking on the viral surface, oligomerization, and complement activation upon antigen recognition 24,30,31 .…”
mentioning
confidence: 99%
“…Atomic force microscopy (AFM) has allowed the imaging of biomolecules under physiological conditions [15][16][17][18][19] , which provides an alternative route to probe Ab-Ag interactions [20][21][22][23] . Previous studies have demonstrated the potential of AFM for imaging Abs with near-atomistic resolution [24][25][26] and its ability for quantitatively mapping nanomechanical forces of Ab-Ag interactions at the single-molecule level [27][28][29] . Recently, high-speed (HS) AFM offers up to video-rate temporal resolution, revealing certain types of dynamic processes of IgGs, e.g., walking on the viral surface, oligomerization, and complement activation upon antigen recognition 24,30,31 .…”
mentioning
confidence: 99%
“…pathways [28][29][30] and receptor-ligand interactions [31][32][33][34] . Singlemolecule FRET (smFRET) is capable of measuring distances at the molecular scale 35 , and has been used to study protein dynamics 36,37 and to characterize structures of receptor-ligand complexes 38,39 .…”
mentioning
confidence: 99%
“…For example, high-affinity non-covalent interactions including Ni:His-tag and Biotin:Avidin have both been used as immobilization tags onto surfaces or as the object of study in AFM-SMFS (Fritz et al, 1998;Berquand et al, 2005;Dupres et al, 2005;Li et al, 2019), as shown in Figure 1B. Many different classes of receptor-ligands have been probed by AFM (Milles et al, 2017;Liu et al, 2019), including antibody-antigen interactions (Dammer et al, 1996;Hinterdorfer et al, 1996Hinterdorfer et al, , 1998Allen et al, 1997;Ros et al, 1998;Schwesinger et al, 2000;Kienberger et al, 2005;Sulchek et al, 2005Sulchek et al, , 2006Neuert et al, 2006;Odorico et al, 2007;Morfill et al, 2008;Roy et al, 2010;Bizzarri and Cannistraro, 2014;Klamecka et al, 2015;Tsai et al, 2016;Liu et al, 2019Liu et al, , 2020, avidin systems (see below), bacterial adhesion systems (Herman et al, 2014;Schoeler et al, 2014;Jobst et al, 2015;Nash et al, 2016;Alonso-Caballero et al, 2018;Herman-Bausier et al, 2018;Milles et al, 2018;Viela et al, 2019), and others (Sletmoen et al, 2004;Farrance et al, 2013).…”
Section: Measurement Configurations For Afm-smfsmentioning
confidence: 99%